An Analysis of Lecturers’ Reinforcement at English Education Department State Islamic of University Sulthan Thaha Saifuddin Jambi - Silvinia, Merlisa (Magister Pendidikan Bahasa Inggris Universitas Jambi, 2024)
This study aimed to explore the use of reinforcement strategies by lecturers during English teaching in the first semester at the English Education Department of the State Islamic University of Sulthan Thaha Saifuddin Jambi. A qualitative case study design was employed, using two data collection methods: an observation checklist and interviews. Five lecturers, each with over eight years of teaching experience in the department, participated in the research. Data were analyzed through three key stages: data reduction, data display, and conclusion drawing. The findings revealed that the lecturers used two types of reinforcement in the English Language Teaching (ELT) classroom: verbal and non-verbal. Verbal reinforcement included the use of words and sentences, while non-verbal reinforcement involved gestures, proximity, and smiles. Reinforcement was delivered in four ways: individually, in groups, through physical proximity, and through a combination of verbal and non-verbal strategies. The most commonly used form of reinforcement was adapted based on students’ performance and classroom conditions.